The Construction of Practical Teaching System for Broadcast Media Major in the Omni-Media Era - Zhou, Zhiling (Journal of Educational Research and Policies, 2025)
For Broadcast Media programs in the Omni-media Era, the design of practical teaching systems requires alignment with media-technology convergence trends, necessitating scalable pedagogical frameworks that integrate cross-platform competencies. The Omni-media Era presents both new opportunities and challenges for Broadcast Media programs, where constructing a demand-responsive practical teaching system has become pivotal to cultivating competent media professionals. Strategic refinement of practical pedagogy—through content optimization, diversified platform development, faculty capacity building, and assessment system enhancement—enables cultivation of future-proof media professionals. Graduates equipped with four core competencies (cross-platform communication, data literacy, creative thinking, collaborative agility) will fulfill industry transformation needs, thus propelling disciplinary evolution in the converged media landscape.